A guide to regional analgesia for Total Knee Arthroplasty. Issue 12 (December 2021) - Rodriguez-Patarroyo, Fabio A.; Cuello, Nadin; Molloy, Robert; Krebs, Viktor; Turan, Alparslan; Piuzzi, Nicolas S.
Abstract : Regional analgesia has been introduced successfully into the postoperative pain management after total knee arthroplasty, reducing pain scores, opioid use and adverse effects. Combination of regional analgesia techniques is associated with better pain management and lower side effects than single regional techniques. Adductor canal block provides good analgesia and considerably lower detrimental effect in muscular strength than femoral nerve block, enhancing surgical recovery. Infiltration techniques may have equivalent analgesic effect than epidural analgesia and peripheral nerve blocks, however there should be awareness of dose dependent toxicity. Novel long-acting local anesthetics role for regional analgesia is still to be determined, and will require larger randomized trials to support its advantage over traditional local anesthetics. Cite this article: EFORT Open Rev 2021;6:1181-1192. DOI: 10.1302/2058-5241.6.210045